Música, educação e currículo: propostas pedagógicas na educação indígena - Silva, Cainã Queiroz (2019)
The purpose of this study is reflect about new pedagogical proposals in the Licentiate for the training of indigenous teachers of the Federal University of Goiás - UFG. The Intercultural Bachelor's degrees aim to discuss teaching possibilities in which Western and non-western knowledge occupies the formal institution denominated traditionally Western school. Music emerges as a pedagogical proposal for certain indigenous peoples, such as the Krahô and Apinajé.Through the Intercultural Licentiate, teachers and professors establish dialogues between theuniversity and the community for the production of pedagogical political projects in which indigenous knowledge is inserted in the institution without being subjugated to modern science.Therefore, the present work analyzes the pedagogical possibilities and the impasses in theconstruction of an indigenous school.